Adjunctive use of modified Yunu-Jian in the non-surgical treatment of male smokers with chronic periodontitis: a randomized double-blind, placebo-controlled clinical trial. Issue 1 (December 2016) - Zee, Kwan-Yat; Chan, Pui; Ho, Johnson; Lai, Stanley; Corbet, Esmonde; Leung, Wai
Abstract Background Yunu -Jian (YJ) is a Chinese medicine (CM)heat purging formula, which is used to reducewei huo (stomach -heat, SH) and enrichshen yin (kidney -yin, KY). This formula is also commonly used to manage diabetes mellitus and gum/oral inflammation. The activity of YJ can be modified or refined by the addition of other CM herbs and/or minor changes to one of its five key ingredients. The aim of this study was to evaluate the adjunctive use of modified YJ (mYJ) or YJ containing additional osteoblast-stimulating and inflammation-modulating CM herbs in the non-surgical periodontal treatment of smokers with chronic periodontitis in a randomized, double-blind, prospective, placebo-controlled study. Methods Healthy adult male smokers with untreated chronic periodontitis who showed CM syndrome of SH and KY deficiency (KYD) whilst attending a dental teaching hospital from October to December, 2005, were invited to participate in a randomized double-blind, placebo-controlled clinical trial. The trial itself involved the once-daily oral administration of a placebo or mYJ for 3 months as an adjunct to non-surgical periodontal therapy. Several periodontal parameters, including radiographic alveolar bone density, were measured by computer-assisted densitometric image analysis (CADIA) on selected sites, and CM signs of SH and KYD were followed from their baseline values to various time points up to 12 months or the end of study. Results Twenty-five smokers (consumed 25.0 ± 15.3 smoking-pack years, ranged 7.5–80; aged 46.3 ± 6.8 years) with periodontitis and SH and KYD were recruited (Placebo, n = 14; mYJ, n = 11). All of the participants showed good tolerance towards the CM recipe. All of the periodontal parameters had improved after 12-month follow-up, and no statistically significant differences were detected between the control group and test group, except for the higher CADIA values observed compared with the baseline at 12 months for test sites (P  = 0.025). 4/3/3 test vs 14/13/13 control participants had persisting SH and KYD at 6, 9 and 12 months (P  < 0.001), respectively. Conclusions The adjunctive use of mYJ preserved the post-treatment increases in the radiographic alveolar bone density at the study sites and led to an overall improvement in SH and KYD compared with the controls. Trial registration HKU Clinical Trial Register, HKCTR-1848 (www.hkuctr.com/Study/Show/3acbf983831244d29d50b543540bf6e9 )